Expression of the Immune Checkpoint Protein VISTA Is Differentially Regulated by the TGF-β1 – Smad3 Signaling Pathway in Rapidly Proliferating Human Cells and T Lymphocytes - Schlichtner, Stephanie; Yasinska, Inna M.; Ruggiero, Sabrina; Berger, Steffen M.; Aliu, Nijas; Prunk, Mateja; Kos, Janko; Meyer, N. Helge; Gibbs, Bernhard F.; Fasler-Kan, Elizaveta; Sumbayev, Vadim V. (Frontiers in Medicine, 2022)
Immune checkpoint proteins play crucial roles in human embryonic development but are also used by cancer cells to escape immune surveillance. These proteins and biochemical pathways associated with them form a complex machinery capable of blocking the ability of cytotoxic immune lymphoid cells to attack cancer cells and, ultimately, to fully suppress anti-tumour immunity. One of the more recently discovered immune checkpoint proteins is V-domain Ig-containing suppressor of T cell activation (VISTA), which plays a crucial role in anti-cancer immune evasion pathways. The biochemical mechanisms underlying regulation of VISTA expression remain unknown. Here, we report for the first time that VISTA expression is controlled by the transforming growth factor beta type 1 (TGF-β)-Smad3 signalling pathway. However, in T lymphocytes, we found that VISTA expression was differentially regulated by TGF-β depending on their immune profile. Taken together, our results demonstrate the differential biochemical control of VISTA expression in human T cells and various types of rapidly proliferating cells, including cancer cells, foetal cells and keratinocytes.